Lady eve's indiscretion ebook - Burrowes, Grace (Windham, 2013)
USA Today Bestseller! "Burrowes delivers red-hot chemistry with a masterful mix of playfulness and sensuality."—Publishers Weekly Starred Review Lady Eve's Got The Perfect Plan Pretty, petite Evie Windham has been more indiscreet than her parents, the Duke and Duchess of Moreland, suspect. Fearing that a wedding night would reveal her past, she's running out of excuses to dodge adoring swains. Lucas Denning, the newly titled Marquis of Deene, has reason of his own for avoiding marriage. So Evie and Deene strike a deal, each agreeing to be the other's decoy. At this rate, matrimony could be avoided indefinitely...until the two are caught in a steamy kiss that no one was supposed to see. Windham series: The Heir (Book 1) The Soldier (Book 2) The Virtuoso (Book 3) Lady Sophie's Christmas Wish (Book 4) Lady Maggie's Secret Scandal (Book 5) Lady Louisa's Christmas Knight (Book 6) Lady Eve's Indiscretion (Book 7) Lady Jenny's Christmas Portrait (Book 8) Praise for Lady Maggie's Secret Scandal: "A tantalizing, delectably sexy story that is one of the best yet from an author on the way to the top."—Library Journal Starred Review "A delight...strikingly unique characters with realistic emotions and exciting antics."—RT Book Reviews, 4 Stars "Captivating...historical romance at its finest and rife with mystery and intrigue."—Romance Fiction on Suite 101